A recycled PP composite material and preparation method thereof

By introducing modified coated nano calcium carbonate into the recycled PP composite, the problem of brittle fracture and insufficient thermal stability during the continuous processing of recycled PP materials is solved, and the thermal stability and oxidation resistance of the material are improved.

CN118878982BActive Publication Date: 2025-03-18DONGGUAN YUJIE IND INVESTMENT CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411106824.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-13
Publication Date
2025-03-18
Estimated Expiration
2044-08-13

AI Technical Summary

Technical Problem

Recycled PP materials are prone to brittle fracture during the continuous processing, and the finished products are insufficient in thermal stability.

Method used

Modified filler, i.e., modified nano-coated calcium carbonate, is used to form coated nano-coated calcium carbonate through emulsion polymerization and transesterification reaction, and is combined with an activated light stabilizer and added to the recovered PP composite material as a modified filler.

Benefits of technology

The thermal stability and oxidation resistance of the recycled PP composite material are improved, brittle fracture is avoided, and the durability and thermal stability of the material are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004991063600000021
    Figure BDA0004991063600000021
  • Figure BDA0004991063600000071
    Figure BDA0004991063600000071
  • Figure BDA0004991063600000081
    Figure BDA0004991063600000081
Patent Text Reader

Abstract

The present invention relates to a recycled PP composite material and a preparation method thereof, and belongs to the technical field of plastic preparation. The composite material comprises the following raw materials in parts by weight: 100 parts of recycled PP particles, 20-35 parts of modified fillers, and 0.5-1.5 parts of lubricants; the modified filler is a modified coated nano-calcium carbonate, which is obtained by transesterification reaction of coated nano-calcium carbonate formed by emulsion polymerization of hydrophobic nano-calcium carbonate and mixed monomers and an activated light stabilizer; the mixed monomers include methyl methacrylate and 10-undecenoic acid methyl ester. The present invention solves the problem that brittle fracture is prone to occur during the subsequent processing of recycled PP materials, and the thermal stability of the finished product made thereof is insufficient by introducing the modified filler.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of plastic preparation, and in particular, relates to a recycled PP composite material and a preparation method thereof. Background Art

[0002] PP (polypropylene) is a thermoplastic plastic with light specific gravity, high surface hardness, high elasticity, heat resistance, chemical stability, good insulation and other excellent properties. It is widely used in the fields of automotive parts, household appliances, office supplies, etc. Recycled PP came into being to recycle the waste products of these PP products. However, compared with new PP materials, recycled PP materials have lower thermal stability and oxidation resistance due to aging, which makes them prone to brittle fracture during subsequent processing. At the same time, the thermal stability of the finished products made from them is insufficient.

[0003] Therefore, the present invention provides a recycled PP composite material and a preparation method thereof. Summary of the invention

[0004] In view of the above problems, the present invention provides a recycled PP composite material and a preparation method thereof.

[0005] One object of the present invention can be achieved by the following technical solutions:

[0006] A recycled PP composite material, comprising the following raw materials in parts by weight: 100 parts of recycled PP particles, 20-35 parts of modified fillers, and 0.5-1.5 parts of lubricants;

[0007] The modified filler is a modified coated nano calcium carbonate, which is obtained by an ester exchange reaction of coated nano calcium carbonate formed by an emulsion polymerization reaction of hydrophobic nano calcium carbonate and a mixed monomer and an activated light stabilizer;

[0008] The mixed monomer includes methyl methacrylate and methyl 10-undecenoate.

[0009] Furthermore, the emulsion polymerization reaction is specifically performed as follows:

[0010] After the first part of methyl methacrylate, emulsifier, hydrophobic nano-calcium carbonate and deionized water are evenly mixed, the first part of the initiator solution is added dropwise at 75-80°C, and after the addition is complete, the mixture is kept warm and stirred for 1-1.5 hours, cooled to room temperature, and the pH value of the emulsion is adjusted to 9-9.5. The remaining part of methyl methacrylate and 10-undecenoic acid methyl ester are added dropwise at 80-85°C, and at the same time, an aqueous solution containing the remaining part of the initiator is added dropwise. After the addition is complete, the mixture is kept warm and stirred for 4-6 hours to obtain an emulsion containing coated nano-calcium carbonate, which is then spin-dried to obtain coated nano-calcium carbonate.

[0011] Furthermore, the mass ratio of the first part of methyl methacrylate, emulsifier, hydrophobic nano-calcium carbonate, the first part of initiator, the remaining part of methyl methacrylate, 10-undecenoic acid methyl ester, and the remaining part of initiator is 60-70:0.2-1.3:10-20:0.8-1.6:30-40:8-15:0.4-0.8.

[0012] Furthermore, the emulsifier is one of potassium persulfate and ammonium persulfate, and the initiator is one of fatty alcohol polyoxyethylene ether and sodium dodecylbenzene sulfonate.

[0013] Furthermore, the hydrophobic nano-calcium carbonate is obtained by surface modification reaction of nano-calcium carbonate and a silane coupling agent.

[0014] Preferably, the surface modification reaction is performed as follows:

[0015] Nano-calcium carbonate is ultra-dispersed in ethanol, and then a silane coupling agent is added, refluxed for 2-3 hours, filtered, washed, and dried to obtain hydrophobic nano-calcium carbonate, wherein the silane coupling agent is any silane coupling agent well known to those skilled in the art, which can achieve hydrophobic modification of the surface of nano-calcium carbonate, and preferably is silane coupling agent 560.

[0016] Furthermore, the nano calcium carbonate is 250-400nm.

[0017] Preferably, the mass ratio of the nano-calcium carbonate to the silane coupling agent is 10:1-3.

[0018] Furthermore, the molecular structure formula of the activated light stabilizer is shown below.

[0019]

[0020] Furthermore, the activated light stabilizer is produced by the reaction of 2,4-dihydroxybenzophenone and dioxolane-2-one under the action of tetraethylammonium bromide and under the protection of nitrogen.

[0021] Furthermore, the molar ratio of the 2,4-dihydroxybenzophenone, dioxolane-2-one and tetraethylammonium bromide is 1:1-1.5:0.03-0.05, the reaction temperature of the 2,4-dihydroxybenzophenone and dioxolane-2-one is 140-145° C., and the reaction time is 12-24 hours.

[0022] Preferably, the specific operation of the reaction of 2,4-dihydroxybenzophenone and dioxolane-2-one is as follows:

[0023] Mix 2,4-dihydroxybenzophenone, dioxolane-2-one and tetraethylammonium bromide evenly, heat to 140-145°C under nitrogen protection and stirring, continue to keep warm and stir for 12-24 hours, stop the reaction, and perform column chromatography analysis (ethyl acetate: petroleum ether = 1:3 v / v) to obtain an activated light stabilizer.

[0024] Furthermore, the operation of the transesterification reaction is specifically as follows:

[0025] After uniformly mixing the coated nano-calcium carbonate, activated light stabilizer, tetraisopropyl titanate and N,N-dimethylformamide, the mixture is heated to 100-120°C under nitrogen protection and stirring, and the mixture is stirred and reacted for 12-30 hours. The reaction is stopped, filtered, washed and dried to obtain the modified coated nano-calcium carbonate.

[0026] In the above reaction, the reaction between the ester group in the outer layer of the coated nano-calcium carbonate (derived from methyl methacrylate and methyl 10-undecenoate, wherein the long-chain terminal ester group of methyl 10-undecenoate increases the grafting rate of the ester exchange reaction) and the hydroxyl group in the activated light stabilizer is utilized, so that the activated light stabilizer is grafted onto the outer organic layer of the coated nano-calcium carbonate.

[0027] Furthermore, the mass ratio of the coated nano-calcium carbonate, the activated light stabilizer and tetraisopropyl titanate is 10:30-50:1-3.

[0028] The second object of the present invention can be achieved by the following technical solutions:

[0029] A method for preparing a recycled PP composite material, comprising:

[0030] The recycled PP particles, modified fillers and lubricants are added into a twin-screw extruder, and the recycled PP composite material is obtained through melt extrusion and molding.

[0031] Beneficial effects of the present invention:

[0032] The present invention provides a recycled PP composite material and a preparation method thereof, which solves the problem that the recycled PP material is prone to brittle fracture during the subsequent processing and the finished product thereof has insufficient thermal stability by introducing a modified filler.

[0033] The modified filler is a modified coated nano calcium carbonate. First, the excellent toughening and strengthening effect of the rigid particles of nano calcium carbonate is utilized. Moreover, calcium carbonate can also play an excellent thermal stabilization and strengthening role (when the composite material is heated, it absorbs heat and plays the role of a thermal stabilizer). Secondly, the organic layer coated on the outer layer is used as an interface promotion layer to improve the interface performance between the rigid particles and the recycled PP material, and promote the toughening and strengthening effect of the rigid particles. The organic layer of the coated nano calcium carbonate acts as a plasticizing toughening agent, and coordinates with the rigid particles to play a toughening and strengthening role.

[0034] In particular, in the present invention, the coated organic layer contains a polyacrylate flexible chain and a benzophenone light-stable structure, wherein the long-chain ester group on the side of the branch of the polyacrylate flexible chain improves the interaction between the coated organic layer and the polypropylene chain in the recycled PP, that is, improves the role of the organic layer as a plasticizer and toughening agent in the coated nano-calcium carbonate, wherein the benzophenone light-stable structure is anchored in the coated organic layer, which on the one hand improves the antioxidant properties of the composite material, and on the other hand avoids the migration of the benzophenone light-stable structure, thereby improving the durability of the composite material. DETAILED DESCRIPTION

[0035] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0036] Raw materials preparation:

[0037] Hydrophobic Nano Calcium Carbonate:

[0038] 10g of nano calcium carbonate was dispersed in 60mL of ethanol, and then 2.5g of silane coupling agent (silane coupling agent 560) was added, refluxed for 2h, filtered, washed, and dried to obtain hydrophobic nano calcium carbonate, wherein the nano calcium carbonate was 250-300nm.

[0039] Activated light stabilizer:

[0040] 0.1 mol 2,4-dihydroxybenzophenone, 0.12 mol dioxolane-2-one and 0.005 mol tetraethylammonium bromide were mixed evenly, heated to 145°C under nitrogen protection and stirring, and the reaction was continued with heat preservation and stirring for 24 hours. The reaction was stopped and column chromatography analysis (ethyl acetate: petroleum ether = 1:3 v / v) was performed to obtain an activated light stabilizer.

[0041] Example 1

[0042] Coated nano calcium carbonate:

[0043] After 60g of the first part of methyl methacrylate, 0.5g of emulsifier, 20g of hydrophobic nano-calcium carbonate and 200mL of deionized water are evenly mixed, 1.6g of the first part of the initiator aqueous solution is added dropwise at 75°C, and after the addition is complete, the mixture is kept warm and stirred for 1h, cooled to room temperature, and the pH value of the emulsion is adjusted to 9-9.5, and then 40g of the remaining part of methyl methacrylate and 15g of 10-undecenoic acid methyl ester are added dropwise at 80°C, and at the same time, an aqueous solution containing 0.4g of the remaining part of the initiator is added dropwise, and after the addition is complete, the mixture is kept warm and stirred for 6h to obtain an emulsion containing coated nano-calcium carbonate, which is spin-dried to obtain coated nano-calcium carbonate, wherein the emulsifier is potassium persulfate and the initiator is fatty alcohol polyoxyethylene ether.

[0044] Example 2

[0045] Coated nano calcium carbonate:

[0046] After 70g of the first part of methyl methacrylate, 1.3g of emulsifier, 15g of hydrophobic nano-calcium carbonate and 200mL of deionized water are uniformly mixed, 0.8g of the first part of the initiator aqueous solution is added dropwise at 80°C, and after the addition is complete, the mixture is kept warm and stirred for 1.5h, cooled to room temperature, and the pH value of the emulsion is adjusted to 9-9.5, and then 30g of the remaining part of methyl methacrylate and 8g of 10-undecenoic acid methyl ester are added dropwise at 85°C, and at the same time, an aqueous solution containing 0.8g of the remaining part of the initiator is added dropwise, and after the addition is complete, the mixture is kept warm and stirred for 4h to obtain an emulsion containing coated nano-calcium carbonate, which is spin-dried to obtain coated nano-calcium carbonate, wherein the emulsifier is ammonium persulfate and the initiator is sodium dodecylbenzene sulfonate.

[0047] Example 3

[0048] Modified coated nano calcium carbonate:

[0049] After 10g of coated nano-calcium carbonate, 30g of activated light stabilizer, 1g of tetraisopropyl titanate and 80mL of N,N-dimethylformamide are mixed evenly, the mixture is heated to 120°C under nitrogen protection and stirring, and the mixture is stirred and reacted for 30h. The reaction is stopped, filtered, washed and dried to obtain modified coated nano-calcium carbonate (i.e., modified filler).

[0050] Example 4

[0051] Modified coated nano calcium carbonate:

[0052] After 10g of coated nano-calcium carbonate, 50g of activated light stabilizer, 3g of tetraisopropyl titanate and 80mL of N,N-dimethylformamide are mixed evenly, the mixture is heated to 100-120°C under nitrogen protection and stirring, and the mixture is stirred and reacted for 24h. The reaction is stopped, filtered, washed and dried to obtain modified coated nano-calcium carbonate (i.e., modified filler).

[0053] Example 5

[0054] Recycled PP composites:

[0055] 1. Prepare the following raw materials in parts by weight: 100 parts of recycled PP particles, 35 parts of modified filler prepared in Example 3, and 0.5 parts of lubricant (polypropylene wax);

[0056] 2. Add the recycled PP particles, modified fillers and lubricants into a twin-screw extruder, and obtain the recycled PP composite material by melt extrusion and molding.

[0057] Example 6

[0058] Recycled PP composites:

[0059] 1. Prepare the following raw materials by weight: 100 parts of recycled PP particles, 28 parts of modified filler prepared in Example 3, and 1 part of lubricant (polypropylene wax);

[0060] 2. Add the recycled PP particles, modified fillers and lubricants into a twin-screw extruder, and obtain the recycled PP composite material by melt extrusion and molding.

[0061] Example 7

[0062] Recycled PP composites:

[0063] 1. Prepare the following raw materials in parts by weight: 100 parts of recycled PP particles, 20 parts of modified filler prepared in Example 3, and 1.5 parts of lubricant (polypropylene wax);

[0064] 2. Add the recycled PP particles, modified fillers and lubricants into a twin-screw extruder, and obtain the recycled PP composite material by melt extrusion and molding.

[0065] Comparative Example 1

[0066] Recycled PP composites:

[0067] Compared with Example 5, an equal amount of the modified filler in the raw material is replaced with 250-300 nm nano-calcium carbonate surface-modified with silane coupling agent 560, and the rest is the same.

[0068] Comparative Example 2

[0069] Recycled PP composites:

[0070] Compared with Example 5, an equal amount of the modified filler in the raw material is replaced by the coated nano-calcium carbonate prepared in Example 1, and the rest is the same.

[0071] Comparative Example 3

[0072] Recycled PP composites:

[0073] Compared with Example 5, the modified filler in the raw material is deleted, and the rest is the same.

[0074] The physical properties of the recycled PP composite materials obtained in Examples 5-7 and Comparative Examples 1-3 were tested, and the results are shown in Table 1, wherein the tensile strength and elongation at break were tested in accordance with GB / T 1040.2, the UV aging resistance was tested in accordance with GB / T 16422.3, the test time was 168 hours, and then the tensile strength was tested, and the decrease rate of the tensile strength was calculated; the heat aging resistance was tested by placing it in an oven at 90°C for 168 hours, and then taking it out to test its tensile strength, and the decrease rate of the tensile strength was calculated, and the heat deformation temperature was tested in accordance with ISO 75-2.

[0075] Table 1

[0076]

[0077]

[0078] It can be seen from the data in Table 1 that the recycled PP composite materials obtained in Examples 5-7 of the present invention have good elasticity, thermal stability and aging resistance.

[0079] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0080] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. A recycled PP composite material, characterized in that: The raw materials include the following parts by weight: 100 parts of recycled PP particles, 20-35 parts of modified fillers, and 0.5-1.5 parts of lubricants; The modified filler is a modified coated nano calcium carbonate, which is obtained by an ester exchange reaction of coated nano calcium carbonate formed by an emulsion polymerization reaction of hydrophobic nano calcium carbonate and a mixed monomer and an activated light stabilizer; The mixed monomer includes methyl methacrylate and methyl 10-undecenoate; The activated light stabilizer is produced by the reaction of 2,4-dihydroxybenzophenone and dioxolane-2-one under the action of tetraethylammonium bromide and under the protection of nitrogen; The molar ratio of the 2,4-dihydroxybenzophenone to dioxolane-2-one is 1:1-1.5, the reaction temperature of the 2,4-dihydroxybenzophenone and dioxolane-2-one is 140-145° C., and the reaction time is 12-24 hours.

2. A recycled PP composite material according to claim 1, characterized in that: The specific operation of the emulsion polymerization reaction is as follows: After the first part of methyl methacrylate, emulsifier, hydrophobic nano-calcium carbonate and deionized water are evenly mixed, the first part of the initiator solution is added dropwise at 75-80°C, and after the addition is complete, the mixture is kept warm and stirred for 1-1.5 hours, cooled to room temperature, and the pH value of the emulsion is adjusted to 9-9.

5. The remaining part of methyl methacrylate and 10-undecenoic acid methyl ester are added dropwise at 80-85°C, and at the same time, an aqueous solution containing the remaining part of the initiator is added dropwise. After the addition is complete, the mixture is kept warm and stirred for 4-6 hours to obtain an emulsion containing coated nano-calcium carbonate, and coated nano-calcium carbonate is obtained after post-treatment.

3. A recycled PP composite material according to claim 2, characterized in that: The mass ratio of the first part of methyl methacrylate, emulsifier, hydrophobic nano calcium carbonate, the first part of initiator, the remaining part of methyl methacrylate, 10-undecenoic acid methyl ester, and the remaining part of initiator is 60-70: 0.2-1.3:10-20:0.8-1.6:30-40:8-15:0.4-0.8。 4. The recycled PP composite material according to claim 2, characterized in that: The emulsifier is one of fatty alcohol polyoxyethylene ether and sodium dodecylbenzene sulfonate, and the initiator is one of potassium persulfate and ammonium persulfate.

5. The recycled PP composite material according to claim 2, characterized in that: The hydrophobic nano calcium carbonate is obtained by surface modification reaction of nano calcium carbonate and a silane coupling agent.

6. The recycled PP composite material according to claim 1, characterized in that: The operation of the transesterification reaction is specifically as follows: After uniformly mixing the coated nano-calcium carbonate, activated light stabilizer, tetraisopropyl titanate and N,N-dimethylformamide, the mixture is heated to 100-120°C under nitrogen protection and stirring, and the mixture is stirred and reacted for 12-30 hours. The reaction is stopped and the modified coated nano-calcium carbonate is obtained through post-treatment.

7. The recycled PP composite material according to claim 6, characterized in that: The mass ratio of the coated nano calcium carbonate, the activated light stabilizer and tetraisopropyl titanate is 10:30-50:1-3.

8. A method for preparing a recycled PP composite material according to any one of claims 1 to 7, characterized in that: include: The recycled PP particles, modified fillers and lubricants are added into a twin-screw extruder, and the recycled PP composite material is obtained through melt extrusion and molding.

Citation Information

Patent Citations

  • Composite toughening modifier for plastics and preparation method thereof

    CN102464839A

  • Surface modified nano calcium carbonate and preparation method thereof

    CN103224648A